Upaya Meningkatkan Hasil Belajar PPKn Siswa pada Materi Wawasan Nusantara dengan Model Debat - Masrukhan Masrukhan (Universitas PGRI Semarang, 2022)
Interest and active participation of students of class X MIPA 2 MAN 2 Semarang are less on the process of teaching and learning activities that result in the acquisition value Civics achieved in the first daily test lowest of 11 classes with the results of the average value of 27, the number of students who are competent were 3 people, incompetent were 33 people with mastery learning 8,3%, below the minimum completeness criteria 75. Medium mastery learning expected at 85%. Issues that will be examined by using the Debate Model to improve the competence of students to the Archipelago Concept material in accordance with the basic competencies of subjects Civics Madrasah Aliyah class X second semester is to characterize the important meaning of the Archipelago Concept in the Unitary State of the Republic of Indonesia. The study was conducted as a Class Action Research within 4 months starting in January until April 2022 using two cycles. Subjects were students of class X MIPA 2 MAN 2 Semarang who are 34 people. Research findings on the first cycle of students’ participation in general is good, as seen from the results of observations made by teachers, the average value reached by the students was 76, students who are competent as many as 27 people, incompetent were 9 people and mastery learning 75%. However, there is still no satisfaction because mastery learning has not reached 85%, so the study continued with Cycle II in principle as in the first cycle but there were competitions between the students. Cycle II shows the results on the students' participation is better than Cycle I. The average value reached 90, the number of students who qualified 34 people incompetent were 2 people and achieve mastery learning 94%. Based on these findings it can be concluded that the use of Debate Model can enhance students's understanding of the concept of learning about the Archipelago Concept and can increase students’ interest and active role. It is advisable for Civics teachers can be creative in learning innovation and may try to use the Debate Model in learning Civics.